Study on determination of errors in prescription writing: A semi-electronic perspective - Ansari, M; Neupane, D (Kathmandu University Medical Journal, 2010)
Background: Prescription writing is one of the most important and basic skills that a doctor needs. Prescribing errors may have various detrimental consequences. Hence, the components of a prescription should be clearly written, free of drug related omission (incomplete prescription), commission (incorrect information) and integration errors, without nonofficial abbreviations, and fulfil the legal requirements of a prescription. Since errors of prescribing are the commonest form of avoidable medication errors, it is the most important target for improvement. Objectives: To estimate the types and prevalence of medication errors during transcription. Materials and methods: A cross sectional descriptive retrospective study was conducted at Nobel Medical Teaching Hospital, Biratnagar, Nepal during a time period from 15th November 2008 to 14th February 2009. A random sample of 268 prescriptions of patients written during a period of one year (18/06/2007 to 17/06/2008) for ten different medical out patient departments of the Hospital were reviewed and the analysis was carried out for determining the different types of errors in writing a prescription. Results: No error was found regarding the name, age, sex and address of the patients. The error in prescriptions regarding the prescriber's name, qualification, NMC registration number and signature were 85.4%, 99.6%, 99.6% and 15.7% respectively. Similarly, the symbol Rx was missing in 66.8%. Dosage form, quantity, dose, frequency and route of administration were not mentioned in 12%, 60%, 19%, 10% and 63% of the prescriptions respectively. Likewise, strength of the prescribed medicines was not stated in 40% of the cases. Conclusion: There is a need to critically address the legibility of prescription, correct spelling of drugs, authorised abbreviations and all other informations of a prescription concerned with patient, prescriber and drugs to minimise the occurrence of medication errors. Key words: Drugs; Errors; Prescription; Rational; Writing DOI: 10.3126/kumj.v7i3.2730 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 238-241